Corporate Governance in Colombia. Current trends (2019)
This document provides a look at The Colombian Corporate Governance System, from the promulgation of the Law 275 of 2001. The guidelines of international standards on corporate governance are commented and compared with the Colombian legislation. Features of the Code of Good Governance in Colombia are evaluated in which look for get competitiveness, sustainability, and deepening of the stock market, according to the principles of the OECD. It is presented a comparative study make in the country during 2002 and 2007 where there were deficiencies in the codes of the company's investor protection, the role of boards and transparency of information. The author shows a study about the annual penetration in adopting good governance practices in Colombia and concludes that the private financial sector is concerning to adopt them. That study present that 60% of companies have made no changes to the code since its inception.